Work Related Musculoskeletal Complications Experienced by Physical Therapists in Pakistan - Syed Kashaf Ali, Sana Tauqeer, Ammarah Ikram, Hafiza Iqra Rubab, Hafiza Sara Wafa, Syed Mujtaba Ali (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To find out the work related musculoskeletal complications experienced by the physical therapists in Pakistan. Methods: This cross sectional study was conducted on 98 physiotherapists. To gather precise data and address challenges, a self-administered questionnaire was created for demographics. A modified version of the Nordic Questionnaire was used and to locate pain or unpleasant feelings in nine different areas of the body, including the neck, shoulders, elbows, wrists, upper back, lumbar, thighs, knees, and ankles. Utilising a non-probability convenient sampling strategy, the sample size was determined. The Lahore hospitals will be asked for written consent. Data will be gathered from various hospitals in Lahore, including Jinnah Hospital and the UOL teaching hospital. Results: 52% reported that they have feeling trouble in neck during last 7 days. 52% have been feeling any trouble in shoulders. 47.9% have been feeling any trouble in upper back. 41.8% have been feeling any trouble in elbows. 41.8% have been feeling any trouble in wrist/ hands. 60.2% have been feeling any trouble in lower back. 29.5% have been feeling any trouble in hips/thighs. 26.5% have been feeling any trouble in knees. 30.6% have been feeling any trouble in ankles/feet. Conclusion:Physical therapists from Pakistan frequently suffered from work-related musculoskeletal conditions, particularly in the neck, shoulders, wrist, and lower back. Keywords: Physiotherapist, Musculoskeletal, Complications